Hubungan Antara Persentase Hati Dan Sekum Terhadap Tingkat Keparahan Penykit Koksidiosis Ternak Kelinci - Suryani, Tuti; Sufiriyanto, Sufiriyanto; Samsi, Muhammad (ANGON: Journal of Animal Science and Technology, 2019)
Background. The purpose of this study was to determine the relationship between the percentage of liver and cecum to the severity of coccidiosis in rabbits in Banyumas Regency. Materials and Methods. The rabbit samples obtained came from several villages in Bayumas Regency. Analysis of faecal samples using the withlock method in 50 samples of weaning rabbit feces. The methods used in this study are knives, tissues, a set of surgical scissors, plastic, measuring cups, microscopes, pippets, slide withlock, sugar shether, water, scales with a capacity of 100 grams, trays, and counters. This study uses a survey method, and sampling by convenience sampling and using correlation regression analysis. Variables measured were percentage of liver, percentage of cecum and number of oocysts. Results. The results of the percentage study of cecum and liver did not have an effect on the severity of the disease based on the number of oocysts with significance on the percentage of liver 0.704> 0.05 and on the percentage cecum 0.202> 0.05 and a very weak correlation value of 0.055 on the percentage of hearts and 0.184 on the percentage sekum. Conclusion. The total 50 samples analyzed in this study contained eimeria oocyst.